2000
DOI: 10.1103/physrevlett.84.3835
|View full text |Cite
|
Sign up to set email alerts
|

Controlling Chaos with Simple Limiters

Abstract: New experimental results demonstrate that chaos control can be accomplished using controllers that are very simple relative to the system being controlled. Chaotic dynamics in a driven pendulum and a double scroll circuit are controlled using an adjustable, passive limiter-a weight for the pendulum and a diode for the circuit. For both experiments, multiple unstable periodic orbits are selectively controlled using minimal perturbations. These physical examples suggest that chaos control can be practically appl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
64
0

Year Published

2001
2001
2022
2022

Publication Types

Select...
3
3
2

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(65 citation statements)
references
References 14 publications
0
64
0
Order By: Relevance
“…However, Corron et al (2000) present experimental evidence that chaos control can be accomplished using simple limiters and argue that chaos control can be practically applied to a much wider array of important problems than thought possible until recently. This method, which has been analytically and numerically explored by Wagner and Stoop (2000) and Stoop and Wagner (2003), simply restricts the phase space that can be explored.…”
Section: Article In Pressmentioning
confidence: 99%
See 1 more Smart Citation
“…However, Corron et al (2000) present experimental evidence that chaos control can be accomplished using simple limiters and argue that chaos control can be practically applied to a much wider array of important problems than thought possible until recently. This method, which has been analytically and numerically explored by Wagner and Stoop (2000) and Stoop and Wagner (2003), simply restricts the phase space that can be explored.…”
Section: Article In Pressmentioning
confidence: 99%
“…Next, we study the consequences of the limiter method -as suggested by Corron et al (2000) -on commodity price dynamics. Price limiters may easily be implemented in our framework.…”
Section: Simple Price Limitersmentioning
confidence: 99%
“…More insight into the wealth of the limiter control developed by Corron et al [Corron et al, 2000;Corron & Pethel, 2002;Myneni et al, 1999] and applied to this important aeroelastic problem is provided here. Limiter control uses small perturbations, in the form of a novel nonlinear feedback control plant, to neutralize system instabilities.…”
Section: Introductionmentioning
confidence: 99%
“…In practice, the problem of controller complexity is a very crucial issue and two fundamental issues in this direction have been identi ed [38,39]: one is that the cost implication and the density requirement for designing controllers, the other is that the need to make the complexity of the controller to be, at least comparable to, or less than, the device being controlled, if the controlling technique is desired to achieve a useful end far beyond mere scienti c curiosity. Indeed, the entire control goal would be untenable if a simple chaotic system requires a massively complex controller like the controller proposed in [40].…”
Section: Introductionmentioning
confidence: 99%
“…An important aspect of the problem of chaos control is how to realize the control of chaotic system by designing a simple and physically available controller [38], which is particularly signi cant both for theoretical research and practical applications. In practice, the problem of controller complexity is a very crucial issue and two fundamental issues in this direction have been identi ed [38,39]: one is that the cost implication and the density requirement for designing controllers, the other is that the need to make the complexity of the controller to be, at least comparable to, or less than, the device being controlled, if the controlling technique is desired to achieve a useful end far beyond mere scienti c curiosity.…”
Section: Introductionmentioning
confidence: 99%